MODEL MANGSA-PEMANGSA DENGAN FUNGSI RESPON HOLLING DAN PEMANENAN - Mustika Khadijah; Yuni Yulida; Dewi Sri Susanti (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2021)
The mathematical model of prey-predator interaction is one of the stages of solving mathematical problems by simplifying events that occur in mathematical form. In this research, we discuss a prey-predator model using a type II Holling response function without harvesting and a prey-predator model using a type II Holling response function with harvesting. The purpose of this research was to explain the formation of a prey-predator model with a type II Holling response and a preypredator model with a type II Holling response with harvesting, to determine the stability at the equilibrium point of the model, and to create a model simulation using several sample parameters. The results obtained were three equilibrium points for the prey-predator model with type II Holling response without harvesting and two equilibrium points for the prey-predator model with type II Holling response with harvesting. The stability at two equilibrium points of the prey-predator model using the type II Holling response function without harvesting was asymptotically stable and the stability at one equilibrium point in the prey-predator model using the type II Holling response function in the presence of harvesting in the prey population was asymptotically stable. The comparison of numerical simulations showed that the number of predator population without harvesting was greater than the number of predator population with harvesting.